The emerging role of glycolysis and immune evasion in ovarian cancer - Bowen Jin; Zehua Miao; Junjie Pan; Zhen Zhang; Yibei Yang; Yidong Zhou; Yuanxiang Jin; Zheng Niu; Qiaoping Xu (Cancer Cell International)
Abstract Ovarian cancer (OC) is one of the three most common malignant tumors of the female reproductive system, with the highest mortality rate among gynecologic malignancies. Like other tumors, OC cells undergo metabolic reprogramming phenomenon and convert glucose metabolism into “aerobic glycolysis” and generate a high concentration of lactate, i.e., the “Warburg effect”, which provides a large amount of energy and corresponding intermediary metabolites for their survival, reproduction and metastasis. Numerous studies have shown that targeted inhibition of aerobic glycolysis and lactate metabolism is a promising strategy to enhance the sensitivity of cancer cells to immunotherapy. Therefore, this review summarizes the metabolic features of glycolysis in OC cells and highlights how abnormal lactate concentration affects the differentiation, metabolism, and function of infiltrating immune cells, which contributes to immunosuppression, and how targeted inhibition of this phenomenon may be a potential strategy to enhance the therapeutic efficacy of OC.